Penguatan Kesiapan Karier Dalam Program Kampus Mengajar Berdampak Di SMK Negeri 3 Makassar - Nabila Herman; Aswar Aswar; Syahrul Ramadan; Herdiananda Nurhidayah; Asyifa Atzanjani Syarif (Paramacitra Jurnal Pengabdian Masyarakat, 2026)
Graduates of vocational high schools (SMK) in Indonesia currently still face high unemployment. The main problem is the gap between the skills students have and the needs of the workforce, coupled with the fact that many students are not mentally prepared to graduate from school. In response to this, a team from Makassar State University, through the Impact Teaching Campus (KMB) program, conducted counseling guidance activities at SMK Negeri 3 Makassar. This activity aims to make students more prepared to p ursue a career in two ways: by recognizing personality through the RIASEC test and strengthening mental resilience. Involving 32 students from grades XI and XII, the activity was carried out in two stages: mapping career interests and an exciting seminar themed "Life After School." The results showed that the RIASEC test greatly helped students understand their work interests, so they were no longer confused about choosing their future path. In addition, seminars presented through games have proven successful in making students more resilient, better at managing stress, and more adaptable. In conclusion, the combination of clear direction and strong mentality makes students much more prepared to face the working world.